Log in to add a comment

## Answers

a/b=1/3

therefore

b=3a

product of the roots=ab=constant /coeff of x sq.

=ab=12/1

=3=12

=4

a=+/-2

wen a=2,b=6

wen a=-2,b=-6

sum of the roots= -coeff of x/coeff of x sq.

=a+b=-m/1

=+/-8

ans m=+/-8

(+/-2)

The Brainliest Answer!

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Let the roots are x and 3x

we know that sum of roots = -b/a

⇒x +3x = -m

⇒4x = -m

and product of roots = c/a

⇒3x² = 12

⇒x²= 4

⇒x = 2 or -2

so

we know that sum of roots = -b/a

⇒x +3x = -m

⇒4x = -m

and product of roots = c/a

⇒3x² = 12

⇒x²= 4

⇒x = 2 or -2

so

**,when x =2, m = -8****when , x= -2 , m =8**